أثر البرامج الأكاديمية على الخصائص الكمية والنوعية لخريجي التعليم العالي: دراسة ميدانية على أعضاء هيئة التدريس بكليات (الاقتصاد، الآداب، القانون) بجامعة بنغازي (Journal of Academic Research, 2023)
The study aimed to identify the impact of academic programs on the quantitative and qualitative characteristics of graduates of higher education, as well as to identify the impact of the mechanisms used inside the college on the quantitative and qualitative characteristics  of graduates of higher education. The descriptive approach was followed, by using the questionnaire method for data collection, as 176 questionnaires were collected out of the 210 distributed, and the study reached several results, the most important of which are: that the level of academic programs was weak, also The level of mechanisms used inside the college was weak, in addition to the weakness of the level of quantitative and qualitative characteristics of graduates of higher education, and the study also showed a positive effect of statistical significance for academic programs on the quantitative and qualitative characteristics of graduates of higher education, the study also showed that there is a statistically significant positive effect of the mechanisms used to placement of students inside the college on the quantitative and qualitative characteristics of graduates of higher education.